2012
DOI: 10.1016/j.jfma.2011.03.002
|View full text |Cite
|
Sign up to set email alerts
|

The influence of corneal wound size on surgically induced corneal astigmatism after phacoemulsification

Abstract: Mean SIA in the 3.5 mm group was larger than that in the 2.5 mm group in the early postoperative period, but there was no significant difference for the entire observational period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 24 publications
0
10
0
5
Order By: Relevance
“…Factors that are important in recovery of clear, stable vision post‐cataract surgery include resolution of corneal oedema, intraocular inflammation, and stabilisation of corneal astigmatism . With modern techniques of phacoemulsification and foldable IOLs becoming the current standard of care in the Australian health care setting, incision sizes have become smaller, and with smaller incisions comes less induced astigmatism that may take less time to stabilise …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors that are important in recovery of clear, stable vision post‐cataract surgery include resolution of corneal oedema, intraocular inflammation, and stabilisation of corneal astigmatism . With modern techniques of phacoemulsification and foldable IOLs becoming the current standard of care in the Australian health care setting, incision sizes have become smaller, and with smaller incisions comes less induced astigmatism that may take less time to stabilise …”
Section: Discussionmentioning
confidence: 99%
“…Foldable intraocular lenses (IOLs) and phacoemulsification permit increasingly smaller incisions, shorter operative times and decreased disruption to surrounding structures. It has been demonstrated that smaller incisions lead to faster refractive stability following IOL insertion and induce less corneal astigmatism, reducing stabilisation time and improving the clarity of uncorrected vision …”
mentioning
confidence: 99%
“…[1011121314] Although, an astigmatic axis shift is affected by the size, location, and shape of the incision, it was reported that the incision size has a major impact on SIA. [15] The appropriate size for a self-sealing corneal incision is 3.0-3.5 mm,[16] and the allowable limit of the keratometric shift for refraction and visual rehabilitation is approximately 0.50 D.[1213] This can be achieved with a 3.0 mm incision.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that minimising the incision size may decrease SIA and improve wound strength and integrity [3,4].…”
Section: Introductionmentioning
confidence: 99%